Seasonal variation in reproductive behaviour of bushbuck (Tragelaphus scriptus Pallas, 1766) in an equatorial savannah ecosystem - Apio, Ann; Muwanika, Vincent B.; Plath, Martin; Wronski, Torsten (African Journal of Ecology, 2009)
While several authors suggest that bushbuck (Tragelaphus scriptus Pallas) from tropical areas with an approximately bimodal rainfall pattern breed throughout the year, there is also a report of seasonal breeding in this species. In this study, we provide indirect evidence of seasonality in reproduction by analysing behavioural data (e.g. rates of mixed-sex sightings) in a population of bushbuck inhabiting an equatorial savannah ecosystem in western Uganda. Observation rates of mixed-sex sightings were correlated with rainfall patterns. We suggest that peaks in reproductive behaviour following the wet season may be advantageous if calves are born during the next wet season, when fresh vegetation is available.
Keywords: Antelopes; mating behaviour; seasonality; Uganda